2020
DOI: 10.1186/s12957-020-01829-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of chondroblastoma treated using synthetic bone substitute: risk factors for developing radiographic joint degeneration

Abstract: Background: Chondroblastoma (CB) is a rare locally aggressive bone tumor that commonly occurs in the epiphysis or apophysis of long bones. Although surgical treatment of CB carries potential risk for physeal or articular cartilage damage, risk factors for joint degeneration have not been well described. In addition, we have mainly used synthetic bone substitute (SBS) to fill the bone defect after intralesional curettage as treatment for CB. This study thus aimed to evaluate the incidence of and risk factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
7
0
2
Order By: Relevance
“…The use of an intraosseous arthroscope during chondroblastoma excision can improve intralesional visualization, confirm complete tumor excision, and assess cartilage integrity post-excision. Adjuvant treatments can lower local recurrence rates, but should ideally be utilized under direct visualization [ 5 , 6 , 7 , 8 , 9 ] and are made safer by arthroscopic assistance.…”
Section: Discussionmentioning
confidence: 99%
“…The use of an intraosseous arthroscope during chondroblastoma excision can improve intralesional visualization, confirm complete tumor excision, and assess cartilage integrity post-excision. Adjuvant treatments can lower local recurrence rates, but should ideally be utilized under direct visualization [ 5 , 6 , 7 , 8 , 9 ] and are made safer by arthroscopic assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, in the treatment of patients with CB of long bones, thorough tumor curettage with high-speed grinding drills, bone cement filling or radiofrequency ablation can lead to a good long-term prognosis and preserve as much normal function of the limb as possible[ 28 , 29 ]. In addition to chemical (phenol), electrocautery or cryosurgery can be used as adjuvant treatment for CB patients[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Location, age, persist epiphysis and inadequate curettage once were considered a possible risk factor for recurrence, but still lack of reliable evidence or controversial [7,13,24]. Outani H et al [30] reported a 20% recurrence rate in their retrospective study of 40 patients with chondroblastoma, while the univariate analysis did not identify any signi cant risk factors for local recurrence. Ebeid WA et al [4] reported a retrospective study of 91 patients with chondroblastoma and found no statistical signi cance between the incidence of local recurrence and factors including age, sex, pathologic fracture or even the type of ller used.…”
Section: Discussionmentioning
confidence: 99%